The Impact of Age on Perioperative Complications After Minimally Invasive Sacrocolpopexy. Issue 6 (June 2021) - Edge, Preston; Barletta, Kathryn; Patnam, Radhika; Geller, Elizabeth J.
Abstract : Objective: Our aim was to compare perioperative complications between older (≥65 years), middle-age (55–64 years), and younger (<55 years) women after minimally invasive sacrocolpopexy (SCP). Methods: This retrospective cohort study included women undergoing SCP from 2006 to 2016 at a single academic center. Our primary outcome was the rate of perioperative complications (intraoperative and postoperative within 6 weeks of surgery), between groups. Secondary outcomes included readmission and reoperation rates. Results: There were 440 consecutive participants: 159 (36.1%) older, 160 (36.4%) middle-age, and 121 (27.5%) younger women. The overall intraoperative complication rate from SCP was 9.1%, with the most common being cystotomy (5.0%) and vaginotomy (1.8%). There were no differences in intraoperative complications between groups. Urinary tract infection (10.9%) and port-site cellulitis (3.4%) were the most common postoperative complications. For our primary outcome, younger women had a higher rate of postoperative complications compared with middle-age and older women ( P < 0.001). There was no difference in postoperative complications between older and middle-aged women. In a multivariate regression controlling for comorbidity, body mass index, diabetes, smoking status, concomitant hysterectomy, and/or sling, younger women retained a higher rate of postoperative complications (odds ratio, 1.7 [1.2, 2.2]). Rates of readmission (3.2%) and reoperation (0.7%) were also similar between groups. Conclusions: The rate of perioperative complications was low with no difference in intraoperative complications. Women under 55 had a higher rate of postoperative complications compared to women age 55 to 65 years and those older than 65 years. Our results suggest that it is reasonable to offer SCP to women older than 65 years.